Technological characterization of vaginal probiotic lactobacilli: resistance to osmotic stress and strains compatibility - Silva, Jessica Alejandra (2019)
Aims: The aim was to evaluate the osmotic stress resistance of vaginal beneficial probiotic strains, their growth kinetics and parameters when growing in salt-added culture media, and their compatibility to go further in the design of a probiotic formula for reconstitution of vaginal microbiome in women. Methods and Results: The resistance to osmotic stress of the lactobacilli was evaluated by determining their growth in MRS (as control) added with NaCl (2–8%). The most resistant strains were Lactobacillus gasseri CRL1509, L. rhamnosus CRL1332 and L. reuteri CRL1327 selected by statistical approaches and growth parameters. Electron microscopy was applied to determine changes. They maintain probiotic properties and viability. Some strains showed incompatibility, then they cannot be included in multistrain formulas. Conclusions: The resistance to different salt concentrations in vaginal lactobacilli is strain-specific, because the behaviour is different in strains identified into the same species. The resistance is not related to the metabolic groups. Significance and Impact of the Study: The resistance and survival to extreme osmotic resistance is one of the specific requirements of beneficial bacteria after the technological processes for their inclusion in probiotic formulas, in a way to express their beneficial characteristics and exert the effect on the host.